Cardiolipin Strongly Inhibits the Leakage Activity of the Short Antimicrobial Peptide ATRA-1 in Comparison to LL-37, in Model Membranes Mimicking the Lipid Composition of Staphylococcus aureus (2023)
ABSTRACT: Cardiolipin is one of the main phospholipid components of Staphylococcus aureus membranes. This lipid is found at varying concentrations in the bilayer, depending on the growth stage of the bacteria, and as a response to environmental stress. Cardiolipin is an anionic phospholipid with four acyl chains, which modulates the bending properties of the membrane due to its inverted conical shape. It has been shown to inhibit the pore forming activity of several antimicrobial peptides, in general doubling the peptide concentration needed to induce leakage. Here we find that the short snake-derived antimicrobial peptide ATRA-1 is inhibited by several orders of magnitude in the presence of cardiolipin in saturated membranes (DMPG) compared to the human cathelicidin LL-37, which is only inhibited two-fold in its leakage-inducing concentration. The ATRA-1 is too short to span the membrane and its leakage activity is likely related to detergent-like alterations of bilayer structure. Fluorescence spectroscopy shows only a minor effect on ATRA-1 binding to DMPG membranes due to the presence of cardiolipin. However, FTIR spectroscopy shows that the acyl chain structure of DMPG membranes, containing cardiolipin, become more organized in the presence of ATRA-1, as reflected by an increase in the gel to liquid-crystalline phase transition temperature. Instead, a depression in the melting temperature is induced by ATRA-1 in DMPG in the absence of cardiolipin. In comparison, LL-37 induces a depression of the main phase transition of DMPG even in the presence of cardiolipin. These data suggest that cardiolipin inhibits the penetration of ATRA-1 into the membrane core, impeding its capacity to disrupt lipid packing.